EFFECTS OF RESISTANCE TRAINING IN REDUCTION THE PERCENTAGE OF BODY FAT IN ADULTS: A REVIEW OF LITERATURE - Gracieli Grahl; Jahn Thobias Noamann; Renan Hartmann Nunes; Lucinar Jupir Forner Flores (Universidade Estadual do Oeste do Paraná, 2014)
The present study was characterized as a literature and aimed at assessing the current literature about the effects of resistance training (RT) / weight in reducing body fat percentage in adults with overweight or obesity. Thus, we also presented the theoretical aspects, and practical features of the RT and verify that the effect of RT factors such as body fat percentage, body mass and lean mass. It was found that the RT, being nominated for various stakeholders with different objectives. Thus, they have been studying its indication in the treatment of obesity and overweight, because to raise the increase in resting metabolism and increase lean body mass, is likely to have decreased body fat percentage. Porting, it is inferred that the RT is presented as a good alternative to physical exercise programs in order to control overweight and obesity, presenting both preventing these situations and in their treatment changed because the percentage of body fat beneficial, the literature analyzed.